Utharomyces epallocaulus Boedijn. ex Kirk & Benny. A new record from Venezuela - Delgado ívilaAdolfredo; Urdaneta García, Lilia; Piñeiro Chávez, Albino (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> On the basis of a study of coprophilous fungi from Zulia state, Venezuela, a Pilobolaceae (Mucorales) Zygomycota with simple sporangiosphores positively phototropic, arising from terminal or intercalary, subglobose, to ovoid trophocysts formed within the agar, at first erect, later decumbent, was isolated from rat and mouse dung. The sporangia is initially globose and white, and at maturity it is somewhat subglobose and black, echinulate. The subsporangial stalk has little or no pigmentation at this stage. At maturity, the wall of the subsporangial stalk is thickened and pigmented, dark brown near the sporangium but becoming paler toward the vesicle. The sporangiospores are globose to subglobose and ornamental. The specie was identified as Utharomyces epallocaulus, which represents a new record for Venezuela.